Young Learners: Defining Literacy in the Early Years—a Contested Space. Issue 1 (March 2013) - Raban, Bridie; Scull, Janet
WITH THE RECENT PUBLICATION of the Early Years Learning Framework for all Australian children during the years before they start school, there is now for the first time a national document to guide the work of all Australian early childhood educators. This document identifies five learning outcomes designed to capture the integrated and complex learning and development of all children in the birth to five years age range. In particular, learning outcome five addresses children as effective communicators; and one of the key components of this outcome is children gaining meaning from a range of texts. This paper reviews issues surrounding early literacy in the years before school and seeks to identify a definition of early literacy which will clarify early childhood educators' understanding of this important area of young children's learning and development, and support their practice more specifically.